A framework for classifying disassemble/analyse/assemble activities in engineering design education. (21st October 2008) - Ogot, Madara M.; Okudan, Gul E.; Simpson, Timothy W.; Lamancusa, John S.
Disassemble/analyse/assemble (DAA) activities of an artifact pervade many undergraduate engineering courses in the USA as they provide useful 'hands-on' learning components. DAA activities are central to product dissection and reverse engineering activities used by many engineering practitioners as part of their industry's benchmarking and competitive analysis processes. Although the two terms are used interchangeably in the literature and as part of course titles, we argue that they are different activities based on their roles, objectives and outcomes when used in engineering education. This paper presents a classification framework for DAA activities in engineering education that differentiates between product dissection and reverse engineering in the context of the desired educational goals. Relevant examples from existing classes and the literature are presented, and implementation challenges are discussed.